Fish fauna homogenization of the United States, life-history correlates of native extinctions and non-native invasions in the American Southwest, and the bi-directional impacts of dams in the American Southeast - Olden, Julian David, author; Poff, N. Leroy, advisor; Angermeier, Paul L., committee member; Douglas, Michael E., committee member; Fausch, Kurt D., committee member (Colorado State University. Libraries, 2004)
The conservation of biodiversity and preservation of biological integrity are at the forefront of scientific thought and research. An important aspect of the current biodiversity crisis is the manner by which the compositions of biological communities are changing in time and space, and the specific mechanisms responsible for these changes. In the first section of my doctoral dissertation I explore the process of biotic homogenization, by which formerly-distinct native communities become more similar as a result of native species extinctions and the establishment of cosmopolitan, nonnative species. I identify three forms of homogenization (genetic, taxonomic and functional) and explore the immediate and future impacts of each on ecological and evolutionary processes. Next, I present a conceptual model that describes a number of potential scenarios by which species invasions and/or extinctions can lead to various trajectories of biotic homogenization or differentiation (i.e., decreased community similarity). I use a simulation approach to explore the model's predictions and then validate the model using empirical data for freshwater fish faunas in the United States at three spatial scales: the entire continent, zoogeographic provinces in California, and watersheds within these provinces. In the second section of my doctoral dissertation I examine the fish faunas of the Colorado River Basin, where environmental degradation and the proliferation of nonnative fish species threaten the endemic, native faunas, making them especially susceptible to biotic homogenization. Using fish occurrence data for the past 160 years I quantify long-term changes in fish distributions and use a comprehensive suite of morphological, behavioural, physiological and life-history traits to identify specific life-histories strategies that are associated with the greatest loss of native species and spread of non-native species. In the third section of my doctoral dissertation I report on research conducted in the Upper James River Basin that considers one of the primary causes of native extirpations and non-native introductions in aquatic systems; namely the regulation of rivers by dams and diversions. Specifically, I examine how environmental disturbance gradients that occur below a flood-control dam structure (i.e., altered flow regime, water temperatures, substrate composition, and macroinvertebrate biomass) influence the structure of downstream fish assemblages.
Keywords: ecology; aquaculture; fish production; aquatic sciences